Bovine-Derived Xenografts Immobilized With Cryopreserved Stem Cells From Human Adipose and Dental Pulp Tissues Promote Bone Regeneration: A Radiographic and Histological Study - Zhu, Yu; Wei, Shi-min; Yan, Kai-xiao; Gu, Ying-xin; Lai, Hong-chang; Qiao, Shi-chong (Frontiers in Bioengineering and Biotechnology, 2021)
Adipose tissue-derived stem cells (ADSCs) and dental pulp stem cells (DPSCs) have become promising sources for bone tissue engineering. Our study aimed at evaluating bone regeneration potential of cryopreserved ADSCs and DPSCs combined with bovine-derived xenografts with 10% porcine collagen. In vitro studies revealed that although DPSCs had higher proliferative abilities, ADSCs exhibited greater mineral depositions and higher osteogenic-related gene expression, indicating better osteogenic differentiation potential of ADSCs. After applying cryopreserved ADSCs and DPSCs in a critical-sized calvarial defect model, both cryopreserved mesenchymal stem cells significantly improved bone volume density and new bone area at 2, 4 and 8 weeks. Furthermore, the combined treatment with ADSCs and xenografts was more efficient in enhancing bone repair processes compared to combined treatment with DPCSs at all time points. We also evaluated the sequential early bone healing process both histologically and radiographically, confirming a high agreement between these two methods. Based on these results, we propose grafting of the tissue-engineered construct seeded with cryopreserved ADSCs as a useful strategy in accelerating bone healing processes.